Management of Common Bile Duct Stones Encountered During Cholecystectomy in Patients With Previous Gastric Bypass - Popowicz, Agnieszka; Sanamrad, Susanne; Darkahi, Bahman; Zacharias, Rebecka; Sandblom, Gabriel (Frontiers in Surgery, 2021)
Background: Rapid weight loss following gastric bypass (GBP) predisposes to the development of gallstones, and in those who develop gallstone disease there is a high prevalence of common bile duct stones (CBDS). Furthermore, in these patients, CBDS are difficult to extract due to the altered upper gastrointestinal anatomy following GBP. The aim of the present study was to assess outcome after various management methods applied in the counties of Stockholm and Uppsala, Sweden. Methods: Data from the Swedish Register for Gallstone Surgery and ERCP (GallRiks) and the Swedish Obesity Surgery Register (SoReg) were crossmatched to identify all patients who had undergone gallstone surgery after GBP, where CBDS were found at intraoperative cholangiography, in the Stockholm and Uppsala counties 2009–2013. A retrospective review of patient records was performed for all patients identified. Results: In all, 55 patients were identified. These were managed as follows: expectancy (N = 11); transgastric ERCP (N = 2); laparoscopic choledochotomy (N = 3); open choledochotomy (N = 5); transcystic stone extraction (N = 12); and other approach (N = 13). In nine cases, data on management could not be found. There were nine cases of minor postoperative complication. No retained stones were registered. The operation time was longer for transgastric ERCP (p = 0.002), and the postoperative stay was longer following open and laparoscopic choledochotomy (p < 0.001). There was no statistically significant difference between any of the methods regarding the incidence of postoperative complications (p = 0.098). Discussion: Further development of techniques for managing CBDS discovered in patients undergoing cholecystectomy after previous GBP are needed, as well as more comparative studies with greater statistical power.